Practices and Perception of Voluntary Blood Donation Among University Students - Amelia, Mohamad; Madzlifah, Ahadon (College of Pathologists, Academy of Medicine Malaysia, 2024)
Introduction: Blood donation remains the only source of blood and its components. This study aimed to assess the practices and perception of voluntary blood donation among Year 2 medical students of University Malaysia Sarawak and identified factors that hinder their willingness to donate. Materials and Methods: This cross-sectional study involved 118 respondents. A self-administered questionnaire was used, and data were recorded and analysed by using SPSS version 22. Results: Only 27.1% of the respondents had donated blood, while 72.9% never donated blood. Of 32 respondents who had donated their blood, 90.6% were on a voluntary basis. Barriers to donation included unfit to donate (37%), fear of needles (27%), not approached to donate (24%), religious restrictions (3%), fear of knowing health status after donation (3%), no remuneration (1%) and fear blood might be sold (1%). The majority of the respondents (92.4%) perceived that blood donation is a good act, 5.1% of respondents considered it a neutral act, while 2.5% perceived it as a bad act. A majority (79.7%) knew that voluntary donation was the best source of blood. Discussion and Conclusion: Despite the good perception towards blood donation, unfortunately, very few respondents had donated blood. Therefore, it is suggested that awareness-raising programs on the importance of voluntary blood donation should be planned and done so that more donors can be recruited and sufficient blood supply can be maintained.